Functional combbination and its impact on employee productivity - Aziz Alrahman, Rayan Adnan (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to identify the impact of employee’s combination on employee productivity. Researcher used the descriptive-analytical method as an appropriate method for this study. The questionnaire was used as the main tool for collecting data from a random sample of (135) of employees at Al-Noor Specialist Hospital in Makkah Al-Mukarramah, through an electronic form via the (google drive) website. The results of the study concluded that the majority of the study sample of employees agree on the importance of job integration and employee productivity. At a significant level (0.05) for the job integration variable on employee productivity. The results also confirmed that there were no statistically significant differences in the averages of the respondents’ opinions towards job integration and employee’s employee productivity to the variable of gender and years of experience. The study recommended the need for organizations to take advantage of their interest in the employees’ combination by continuing to promote and strengthen that interest in a way that contributes to increasing the level of employee’s combination and in a way that contributes to improving and increasing productivity.